Mechanisms Regulating Endothelial Permeability. (1st December 2014) - Sukriti, Sukriti; Tauseef, Mohammad; Yazbeck, Pascal; Mehta, Dolly
Abstract : The endothelial monolayer partitioning underlying tissue from blood components in the vessel wall maintains tissue fluid balance and host defense through dynamically opening intercellular junctions. Edemagenic agonists disrupt endothelial barrier function by signaling the opening of the intercellular junctions leading to the formation of protein‐rich edema in the interstitial tissue, a hallmark of tissue inflammation that, if left untreated, causes fatal diseases, such as acute respiratory distress syndrome. In this review, we discuss how intercellular junctions are maintained under normal conditions and after stimulation of endothelium with edemagenic agonists. We have focused on reviewing the new concepts dealing with the alteration of adherens junctions after inflammatory stimulus.